Breaking The Seal on the Digital Wallet: A Call to the Legislature for Cryptocurrency Recognition in Sri Lanka - Bandara, J.M.L.S. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
A cryptocurrency is a digital currency, which is transacted independently through computer networks without having a regulation by any central authority. In January 2009, Satoshi Nakamoto introduced bitcoin as the first cryptocurrency in the world and by December 2025, the total value of the global cryptocurrency market was about $3.17 trillion, with bitcoin solely holding a 56.86% dominance. It is evident that, in the contemporary world, various jurisdictions both recognize and prohibit cryptocurrency. However, in Sri Lanka, our law neither explicitly recognizes nor prohibits it. But in 2024, the South Asian Journal of Finance reported that more than 320,000 Sri Lankans held some form of cryptocurrency at that time. Specially, asset declarations recently submitted by Sri Lankan parliamentarians revealed that even some members of the legislature are also included in this category. Therefore, this research primarily explores two issues namely, the potential positive and negative consequences of legalizing cryptocurrency in Sri Lanka, and if so, the extent to which it should be recognized. Both issues were supported with experiences from comparative jurisdictions. This research was based on a qualitative research design, utilizing relevant legislation and other policy documents of Sri Lanka as primary sources, and relevant books, journal articles and internet resources as secondary sources. In overall this demonstrates that, Sri Lanka may enjoy unique advantages in engaging with the global digital economy agenda, strengthening corruption prevention, particularly in relation to money laundering and tax regulation frameworks by legalizing cryptocurrency, while simultaneously facing certain disadvantages relating to monetary policy management and consumer protection. As a result, this research strongly proposes that Sri Lanka’s approach to legalize cryptocurrency must be positioned between El Salvador’s approach, which permits the use of Bitcoin even as legal tender, and China’s approach, which completely bans the use of cryptocurrency.
Keywords: Bitcoin; Cryptocurrency; Digital economy; Legalization; Sri Lanka